Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan di PT Telkom Indonesia Regional 1 Sumatera - Eunike Julianti Christine Telaumbanua; Nursiah Nursiah; Desri Wiana; Agus Edi Rangkuti; Anggiat P. Simbolon (Journal of Management and Creative Business, 2024)
The company's success in achieving its goals and success is supported by several factors, one of which is people. Competent and professional resources will improve the company's performance. Employee performance is the ability, skills, and work results shown by an employee in carrying out his duties and responsibilities at work. Employee performance can be influenced by several factors, including motivation and work discipline. Motivation is an impulse that can trigger a sense of enthusiasm and is also able to change individual behavior towards something better. Besides motivation, work discipline is also a factor that can improve employee performance. Work discipline is the attitude of an employee who respects, respects, obeys and obeys the regulations that apply in the company. The purpose of this study is to determine the influence of motivation and work discipline on employee performance at PT Telkom Indonesia Regional 1 Sumatra. Data was collected through a survey by distributing questionnaires to employees of PT Telkom Indonesia Regional 1 Sumatra. The total population is 89 people and all of them are sampled (saturated samples). The instruments in this study are valid and reliable and the types of data used are primary data and secondary data. The results of the study show that motivation has a positive and significant effect on employee performance Work discipline also has a positive and significant effect on employee performance In this study, it shows that work discipline has a more dominant effect than motivation on employee performance.